1974
DOI: 10.1073/pnas.71.10.3896
|View full text |Cite
|
Sign up to set email alerts
|

A Protonmotive Force Drives ATP Synthesis in Bacteria

Abstract: When cells of Streptococcus lactis or Escherichia coli were suspended in-a potassium-free medium, a membrane potential (negative inside) could be artificially generated by the addition of-the potassium ionophore, valinomycin. In 'response to this inward directed protonmotive force, ATP synthesis catalyzed by the mnembrane-bound'ATPase (EC 3.6.1.3) was observed. (Fig. 1A). Thus, the electrochemical potential of protons (the protonmotive force) provides the driving force for ATP synthesis. The alternative (anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 38 publications
(26 reference statements)
3
103
0
Order By: Relevance
“…and the function of this gene is also still unknown. E. hirae H+-ATPase can synthesize ATP when the proton motive force is imposed artificially (9,40,41,51). These data may suggest that the product of the i gene is not required for either enzyme assembly or enzyme function.…”
Section: Discussionmentioning
confidence: 68%
“…and the function of this gene is also still unknown. E. hirae H+-ATPase can synthesize ATP when the proton motive force is imposed artificially (9,40,41,51). These data may suggest that the product of the i gene is not required for either enzyme assembly or enzyme function.…”
Section: Discussionmentioning
confidence: 68%
“…Since bacterial cells contain more than 200 mM of K' [9,14] and intracellular pH is about 7.5 [lO,lS] , the results presented above are well explained by that the transient motility was induced by an artificial protonmotive force, which was created either by the diffusion potential of K+ brought about by valinomycin (interior negative) or ApH due to pH drop (interior alkaline), or both. A low yield of the motile fraction by the pH drop alone may indicate that the ApH produced under the condition was not enough to support the translational swimming.…”
Section: Motility Induced By An Artificial Protonmotive Jbrcementioning
confidence: 61%
“…Since the intracellular ATP concentration of enteric bacteria has been reported to be about 3 mM (4,26,29,58; for a review, see reference 37), we concluded that the concentration of acetyl-P is also about 3 mM. Implicit in this calculation is the assumption that all three of the phosphates within ATP are turned over at approximately the same rate.…”
Section: Discussionmentioning
confidence: 95%